Gadolinium labelled nanoliposomes as the platform for MRI theranostics: in vitro safety study in liver cells and macrophages - Šimečková, Pavlína; Hubatka, František; Kotouček, Jan; Turánek Knötigová, Pavlína; Mašek, Josef; Slavík, Josef; Kováč, Ondrej; Neča, Jiří; Kulich, Pavel; Hrebík, Dominik; Stráská, Jana; Pěnčíková, Kateřina; et al. (Scientific reports, 2020)
Gadolinium (Gd)-based contrast agents are extensively used for magnetic resonance imaging (MRI). Liposomes are potential nanocarrier-based biocompatible platforms for development of new generations of MRI diagnostics. Liposomes with Gd-complexes (Gd-lip) co-encapsulated with thrombolytic agents can serve both for imaging and treatment of various pathological states including stroke. In this study, we evaluated nanosafety of Gd-lip containing PE-DTPA chelating Gd+3 prepared by lipid film hydration method. We detected no cytotoxicity of Gd-lip in human liver cells including cancer HepG2, progenitor (non-differentiated) HepaRG, and differentiated HepaRG cells. Furthermore, no potential side effects of Gd-lip were found using a complex system including general biomarkers of toxicity, such as induction of early response genes, oxidative, heat shock and endoplasmic reticulum stress, DNA damage responses, induction of xenobiotic metabolizing enzymes, and changes in sphingolipid metabolism in differentiated HepaRG. Moreover, Gd-lip did not show pro-inflammatory effects, as assessed in an assay based on activation of inflammasome NLRP3 in a model of human macrophages, and release of eicosanoids from HepaRG cells. In conclusion, this in vitro study indicates potential in vivo safety of Gd-lip with respect to hepatotoxicity and immunopathology caused by inflammation.
Keywords: Cells, Cultured; lidé; magnetická rezonanční tomografie; inflamasomy; diethylentriaminpentaacetát gadolinia; Magnetic Resonance Imaging; Nanoparticles; makrofágy; hepatocyty; fosfatidylethanolaminy; Contrast Media; nanočástice; kultivované buňky; Humans; Hepatocytes; Gadolinium DTPA; nosiče léků; fibrinolytika; Fibrinolytic Agents; protein NLRP3; NLR Family, Pyrin Domain-Containing 3 Protein; kontrastní látky; Liposomes; Drug Carriers; Macrophages; Phosphatidylethanolamines; Inflammasomes; liposomy